PSXV-12 What 30 years of accumulated pregnancy data taught us about the Bos indicus influence on reproductive performance of beef cattle. (8th October 2021) - Martins, Thiago; Rocha, Cecilia Constantino; Driver, Joseph D; Rae, Owen; Elzo, Mauricio A; Mateesku, Raluca; Binelli, Mario
Abstract: Bos taurus X Bos indicus crossbreeding is commonly used in tropical and subtropical regions to enhance beef production. The effect of Bos indicus genetics on pregnancy to AI (P/AI) and AI + natural service (P/AI+NS) is understudied. We measured the indicus effect from a 30-year dataset of the University of Florida multibreed herd (MBH; n= 7105 animals). The MBH is composed of six breed groups, according to the following proportion of Brahman: 0–19%, 20–34%, 37% (Brangus), 40–59%, 60%-78% and 79%-100%. Estrus of all animals was synchronized using mainly the SelectSynch+CIDR protocol, followed by three-day AI based on heat or timed-AI (TAI) for non-heat animals. After TAI, animals were bred by NS. Breeding seasons lasted 91±18d. Pregnancy was diagnosed by rectal palpation and/or ultrasonography 30d after AI and 30d after removal of bulls. P/AI was affected negatively (P < 0.001) by the proportion of Brahman, regardless of parity, but P/AI+NS was similar across breeding groups (Table 1). By logistic regression, each 1/32 nd increment of Brahman influence reduced odds of P/AI by 0.5% (0/32 nd = 51.4% to 32/32 nd = 35.3%). The variables of body condition score (BCS), days post-partum (DPP) and body weight at the beginning of synchronization protocol did not explain the negative effect of indicus genetics on P/AI. However, indicus genetics were associated negatively with the proportion of animals AIed in heat (P < 0.001). AI in heat resulted in twice as great (P < 0.001) P/AI (65.4%; n = 984) than no-heat TAI (30.9%; n = 829). In conclusion, indicus genetics did not influence overall pregnancy rates at the end of a 90d breeding season. Nevertheless, indicus influence dampened estrus responses to protocols based solely on GnRH-PGF and progestin/progesterone, resulting on suboptimal P/AI (< 40%).